Diadic conditionals of senior high school students’ policultural competence development (Pedagogy of Higher and Secondary Education, 2016)
Furt D. V. Diadic conditionals of senior high school students’ policultural competence development.Nowadays there are many problems in Ukrainian education environment, that’s why it is necessary to create such conditions that some psychological merits can be created in the senior high school students’ minds. In the article the main didactic conditions of senior high school students’ policultural competence development at English lessons are described. The views of some scientists on this problem are considered. The notion «didactic conditions» is identified. The condition is a situation in which something is created or developed. The main forms of work with senior high school students for successful development of the policultural competence are considered. Necessary factors for effective work are identified.It is very important to integrate policultural information with main school curricula of major subjects because it is almost impossible to develop policultural competence only at the English lessons.It should be noted that the policultural competence effectiveness depends on the relationship of academic and extracurricular activities (clubs, exhibitions, contests, conferences, meetings etc.).The next condition for policultural competence development is defined as one that helps to create a cultural space for successful policultural conscience development and self-realization in the family or youth organizations.Cultural environmental organization at school is when students, considering their traditions and stereotypes, may act independently in gaining practical experience and reveal the world of different cultures. Senior high school students’ evaluation other individuals without stereotypes, the critical and logical thinking development are the results of cultural environmental organization; it depends on the variability of foreign languages training programs.So, didactic conditions can encourage policultural education of senior high school students’ process; they help students to create their own life position and to accept other different cultures without critical attitude to them.Didactic conditions are the circumstances of the learning process; they are the result of purposeful selection and usage of teaching methods that make the development of policultural competence successful.
Keywords: conditions; didactic conditions; policultural competence; the development of policultural competence; senior high school students; forms of work; cultural environmental; training programs